Discussion of Fracture Criteria in Spall Mechanics - Chevrier, P.; Klepaczko, J.R. (Engineering Transactions, 1997)
An analysis of variety of spall criteria is discussed in this paper. Some mechanisms of the free surface creation in spall are discussed, including cleavage and fibrous separation. Existence of those micromechanisms of fracturing is illustrated by several fractograms for aluminum alloy, iron and steel. Finally, three groups of fracture criteria used in prediction of spalling are reviewed. It is concluded that all modern spall criteria must have an evolutionary character, that is they must take into account the time evolution of damage. A relatively new simple criterion based on the Boltzmann statistics is verified for 7020-T6 aluminum alloy. This simple criterion appeared to be quite efficient in finite elements computer codes.